ANALISIS HUBUNGAN PEMEGANG SAHAM DENGAN PERUSAHAAN PADA KEBIJAKAN DIVIDEN - Ali Muhayatsyah; Sjafrudin Sjafrudin (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2018)
Signaling theory explains that dividend policy is information that has value. The market will react positively if there is a dividend increase. Increasing dividend payments will be followed by an increase in stock prices, because the company has value. Announcement of dividends is responded by the market quickly when there is an abnormal return at the time of the announcement (informationally efficient market). If investors react to the information content of dividend announcements that have economic value and have a positive impact on the company, then the reaction is the right reaction (decisionally efficient market). Keyword: Dividend Policy, Signaling Theory, Efficient Market.